College students’ preferences and perceptions of online learning activities in a private school in Cavite - Elgien Padohinog; Nilda Balsicas (CV Rezki Media, 2023)
The Covid-19 pandemic has generally disrupted students in their traditional learning which forced them to abruptly shift to the online learning. This descriptive survey research determined the preferences and perceptions of college students in the online learning. A total of six hundred and seventy-nine (679) students in St. Dominic College of Asia in Cavite took part in the survey that was conducted from November to December 2020. A researcher-made questionnaire was developed, validated, and reliability-tested. The online survey was made via Microsoft Forms and was distributed through the Blackboard App and e-mail. Results showed that majority of the students used mobile phones or smartphones for their online learning. Moreover, majority of the students expected that they can listen to an online lecture, which has the highest expectation of students in the online learning. Majority of the students have moderately agreed to their preferred online activities. These include listening to the lecture of the teacher during synchronous meetings and reading the articles according to their own pace or time among others. Implications include those increased utilization of interactive activities with students and integration of innovative and creative approaches to synchronous and asynchronous mode of teaching and learning delivery.